A Study on Factors Affecting Vasectomy in Ahmedabad City of Gujarat - Bhavna T Puwar; Vaibhavi D Patel; Sheetal Vyas (Medsci Publications, 2017)
Background: Out of all the family planning methods available vasectomy is the least preferred method. Objectives: The objective of the study was to study various factors affecting vasectomy. Methods: Record based study with a qualitative component Records of 50% beneficiaries (136) out of total 260 vasectomy operation done in 2014-15 in Ahmedabad city were studied and 10% were interviewed . Data was analyzed using Epi info software. Result: Mean age of the vasectomy beneficiaries was 37.9 years ( SD 6.0) .Mean number of children with the couple were 2.44.Mean age of the last living child was 7.7 years (SD 5.5) .About more than half of the beneficiaries had two children. The last living child was male in 56% and 91% (124) couple had at least one male child in the family. Education of the husband was statistically significantly related to the age of deciding vasectomy and total number of children. Personal interview with beneficiaries revealed that in 12 out of 13 beneficiaries it was a joint decision of the couple .Wife and health worker were the main motivators. They were not told about precautions to be followed till sterilization is achieved. Conclusion: Vasectomy is a less preferred method because of various myths associated with it.